Contractors’ Perception in Integrating Circular Economy in Industrialised Building System (IBS) - Yunus, Riduan; Mohd Nizam, Eizzad Amirul Arash; Mohammed, Mimi Nahariah Azwani; Abdullah, Siti Norain; Trigunarsyah, Bambang (International Journal of Integrated Engineering, 2026)
Industrialised Building System (IBS) is well-recognised in improving sustainable deliverables for construction projects. However, the lack of integration of a circular economy (CE) in IBS construction hinders the continual use of resources and limiting waste elimination. This study investigated the IBS contractors’ perceptions of integrating CE in managing construction and demolition (C&D) waste. The STEEP (Social, Technological, Economic, Environmental and Political) matrix adopted in this study determined the drivers, enablers, challenges, and barriers to integrating CE into the IBS application. Twenty respondents from IBS construction companies participated in semi-structured interviews to provide insights into integrating CE in C&D waste management. The results highlighted that IBS contractors in Malaysia strongly associated CE with waste separation activities, reduction of waste generation, recycling and re-use materials of building components to extend its value. Although CE harbours greater potential in terms of the level of circularity (refuse, rethink, reduce, reuse, repair, refurbish, remanufacture, re-purpose, recycle and recover), the limited knowledge of CE among IBS contractors has hindered the optimisation of IBS from contributing to sustainability. Building on the STEEP matrix, the outcomes of the study initiate further study to determine strategies to improve efficient integration of CE in managing C&D waste for IBS projects.